The effect of laser shock peening with and without protective coating on intergranular corrosion of sensitized AA5083. (January 2022) - Kaufman, Jan; Racek, Jan; Cieslar, Miroslav; Minárik, Peter; Steiner, Matthew A.; Mannava, Seetha R.; Vasudevan, Vijay K.; Sharma, Anurag; Böhm, Marek; Brajer, Jan; Pilař, Jan; Pína, Ladislav; et al.
Abstract: Laser Shock Peening with (LSP) and without protective coating (LPwC) was applied to sensitized AA5083 followed by electrochemical analysis. Potentiodynamic tests indicated a region of increased passivity for the LPwC samples with lower corrosion current. Similarly, significantly reduced intergranular corrosion rate was observed during potentiostatic polarization after LPwC treatment while LSP samples showed only a negligible improvement. The results are attributed to the unique recast surface layer composed of a modified oxide film followed by an embedded oxygen-rich aluminum nanoparticles sub-surface layer without grain boundary β-phase created during laser pulse interaction with the surface when no coating was applied. Highlights: LPwC creates passive region and increases breakdown potential of sensitized AA5083. Recast surface after LPwC protects samples against intergranular corrosion. LPwC applied underwater provides higher protection against intergranular corrosion. LSP refined microstructure is too thin to affect intergranular corrosion. Both LSP and LPwC create compression on sample surface.